THE EFFECT OF FINANCIAL CONSTRAINTS ON FINANCIAL PERFORMANCE WITH EMPLOYEE TURNOVER LEVEL AS A MEDIATION VARIABLE IN NON-CYCLICALS CONSUMER COMPANIES GOING PUBLIC IN INDONESIA IN THE PERIOD 2018 – 2024 - Niar Irba; Risky Budianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effect of financial constraints on financial performance with employee turnover as a mediating variable in Consumer Non - Cyclicals companies listed on the Indonesia Stock Exchange during the 2018 – 2024 period. The research problem arises from increasing financial pressure, particularly during the COVID-19 pandemic, which potentially affects workforce stability and corporate financial performance. This study employs a quantitative explanatory approach using panel data, analyzed through random effects regression and mediation testing, with robustness checks using the KZ Index and SA Index. The results indicate that financial constraints have a negative effect on financial performance and a positive effect on employee turnover. However, employee turnover does not mediate the relationship between financial constraints and financial performance. Future research is encouraged to apply alternative measures of firm performance and incorporate organizational or behavioral variables to better explain the internal mechanisms underlying this relationship.